Penerapan Teknologi Budidaya Tanaman Jahe di Pekarangan Berbasis Pertanian Sehat di Desa Bokor, Kabupaten Malang - Husni Thamrin Sebayang; Kartika Yurlisa; Eko Widaryanto; Nurul Aini; Nur Azizah (Jurnal Pengabdian Pada Masyarakat, 2020)
APPLICATION OF GINGER PLANT CULTIVATION TECHNOLOGY IN THE YARD BASED ON HEALTH AGRICULTURE IN BOKOR VILLAGE, MALANG DISTRICT. House yard is one of the lands that have the potential to be developed. The yard can be used by growing high-value commodity crops. To get high yields and productivity, Farmers must choose the right and proper cultivation techniques. Besides, to get the results in the form of healthy food products, the cultivation process must be carried out by reducing the input of chemical compounds into the farm business. Therefore, community service activities were carried out in Bokor Village, Tumpang Subdistrict, Malang Regency. It was aimed to utilize the house yard by planting ginger based on healthy agriculture. The target group is farmers in the Subur Farmers Group. The stages of activities which were carried out were counseling on the use of house yards, training in ginger cultivation, providing assistance in planting materials and media, and making demonstration plots. The results of community service show that farmers want to try to use the yard by planting ginger in their yard. It also increased knowledge of farmers about ginger cultivation following Good Agricultural Practice so that the use of the yard with proper agriculture-based ginger cultivation can be developed.